PENGARUH PROPORSI DAUN BELUNTAS (Pluchea indica less) DAN TEH HIJAU TERHADAP AKTIVITAS ANTIOKSIDAN PRODUK MINUMAN - Setiokusumo, Christine; Widyawati, Paini Sri; Budianta, Dwi Wibawa (Jurnal Teknologi Pangan dan Gizi, 2016)
Beluntas has many benefits especially on its leaves because of the phytochemical contents. Therefore, beluntas needs to be combined with other ingredient that can increase the antioxidant activity. One of ingredient that can be combined with beluntas is green tea. Green tea is a beverage that is often consumed and has various health benefits, because of the polyphenol compound contents from flavonoid group, mainly catechins. This research was aimed to determine the effect of beluntas leaves and green tea proportion on antioxidant activity of beverage product. The design of this research used single factor randomized block design. Factors that were researched were beluntas leaves and green tea proportion with five level factors, which were P1, P2, P3, P4 and P5. The results showed that the proportion of beluntas leaves and green tea powder significantly affected on phytochemical compounds, total phenol, total flavonoids, DPPH scavenging activity, and iron ion reducing power. Phenolic content was ranged from 451.13-707.63 mg GAE/L sample, flavonoid content was ranged from 95.73-413.73 mg CE/L sample, DPPH scavenging activity was ranged from 193.38-277.79 mg GAE/L sample, and iron ion reducing power was ranged from 211.50-499.50 mg GAE/L sample. Total phenolic and total flavonoid contents were positively correlated with the ability to scavenge free radical DPPH and the ability to reduce iron ion. This means that the higher of phenolic and flavonoid contents in beluntas green tea beverage had the higher the antioxidant capacity. The results showed that P3 had the highest antioxidant activity.